Meal timing and metabolic regulation: the emerging role of chrononutrition - Woźniak, Weronika Maria; Winiarska, Zuzanna; Witczak, Katarzyna Wiktoria; Wieleba, Marcin; Malec, Julia Anna; Wiercioch, Eliza; Włodarczyk, Franciszek; Krupska, Barbara Izabela; Zapalska, Magdalena; Kulig, Lidia (Quality in Sport, 2026)
Background. In recent years, in the context of the growing burden of metabolic diseases, increasing attention has been paid to novel dietary approaches, among which the concept of chrononutrition has gained considerable interest. It focuses on the relationships between meal timing and circadian rhythms, as well as their potential impact on metabolic regulation. Aim. The aim of this study was to present the current state of knowledge regarding the influence of meal timing and circadian rhythms on metabolic processes and metabolic health. Material and methods. A narrative literature review was conducted using the PubMed and Scopus databases, including publications from 2020 to 2026. Original studies and review articles, including systematic reviews and meta-analyses addressing chrononutrition and its potential health implications, were included. Results. Available evidence suggests that synchronization of food intake with circadian rhythms may promote more favorable regulation of glucose and lipid metabolism. Strategies such as time-restricted eating (TRE) may support weight reduction and improve selected metabolic parameters. However, their effectiveness appears to depend, among other factors, on the timing of the eating window. Unfavorable patterns, such as skipping breakfast or late-night eating, have been associated with impaired metabolic control and an increased risk of metabolic disorders. Overall, the findings across studies remain heterogeneous. Conclusions. Meal timing may represent an important component of metabolic regulation and complement traditional dietary approaches. However, due to limitations of the current evidence, further well-designed studies are required to clarify its role in clinical practice.